Examining the Impacts of Covid-19 on Refugees and IDPS - Olagbadegun, Opeyemi M.; Folarin, Sheriff F. (Covenant University Journal of Politics and International Affairs, 2021)
The Coronavirus disease (Covid-19) which started out in Wuhan China and from there spread out to other parts of the world is leaving some devastating effects in its trail. Like the rest of the world, the humanitarian setting is not left out but, those in the humanitarian setting, refugees and IDPs, are amongst the most vulnerable groups in the world. As a result, this study examines the impact the on-going global pandemic has had, and is having on the humanitarian setting with focus on the refugees and Internally Displaced Persons (IDPs). The qualitative research method was employed in achieving this, and data was derived from secondary sources like organisational reports, journal papers, and publications on credible websites. Findings of the study show that the state of lack of facilities, congestion, and poverty that characterises many refugee and IDP camps, makes them more susceptible to the effects of the crisis. The health, education, and basic day to day living of these refugees have been affected. Also, some refugees have had their rights violated by countries under the guise of covid-19 preventive measures. The lockdown adopted as a preventive measure and the testing requirements by governments of some refugees have prevented those who want to return home from doing that. Additionally, the humanitarian sector needs more than ever, all the donations it can get at a time when donor countries are experiencing reducing donating power. The study concludes that in the face of a global pandemic, the refugees and IDPs are plunged into deeper humanitarian needs. Among the recommendations put forward by this study, while prevention and treatment facilities are being made available to address the outbreak of the virus among these groups, host countries should be given more support than ever by various humanitarian organisations.